Peningkatan Kemampuan Menulis Karangan Deskripsi Berbahasa Inggris Melalui Penerapan Model Pembelajaran Kooperatif Think-Pair-Share Siswa Smk Pariwisata Harapan Denpasar - Arimbawa, Kadek (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana; Vol 23 (2016): September 2016)
This study aims to improve students writing skill in doing descriptive text by using cooperative learning type think pair share . The application of both these techniques in teaching and learning proses are expected to solve the problem that are faced by students at grade X UPW II SMK Pariwisata Harapan Denpasar. This research also aims to describe the students’ ability in doing descriptive writing, the improvement of students score, and the aspects that affect students’ success. This study applied a classroom action research design which applies four steps namely planning, action, observation, and reflection. The subjects of this research are 29 students of grade X UPW II SMK Pariwisata Harapan Depasar. This research is conducted into one cycle by applying those four steps action research design. Data collection is done by conducting observation, taking note, documentation, questioner, and written test. Analyzing data is done by describing the result of qualitative and quantitative data. The result of data analysis is presented into table and chart as well as is described into narrative sentences. The improvement of students’ writing skill in doing descriptive text are proven by the result of qualitative data, such as the result of observation, taking note, documentation, and questioner; and quantitative data, such as the result of students’ test. These improvements are shown based on the differentiation mean score betwee pretest, and cycle I. The significance of students’ score improvement occurs in this cycle.
Keywords: think pair share,the improvement of students’ achievement, descriptive text